Botswana Mining Investment and Governance Review - World Bank Group (World Bank, Washington, DC, 2016)
The Botswana Mining Investment and Governance Review (MInGov) collects and shares information on mining sector governance, its attractiveness to investors and how its activities affect national development. It reviews sector performance from the perspective of three main stakeholder groups – government, investors in the mining value chain and civil society – and identifies gaps between declared and actual government policy and practice. The reviews findings are: Performance across the minerals value chain is better in the latter stages related to investment, accumulation, and expenditure of mineral revenue. The mining policy and legal framework are largely sound. The environmental protection legislation is quite current and mostly based on ‘good practice’ except for access to Environmental Impact Assessments. Land use issues, including resettlement and compensation, require a more inclusive process and stronger legislated framework. A local content policy for the mining industry should be developed with mining sector participation to ensure that both the needs of government and industry are met. Institutions are for the most part staffed with trained, qualified people although sometimes there are not sufficient numbers of staff with the required experience. The top shared priority by all three stakeholder groups is Sector Management and Intragovernmental Coordination. MInGov’s methodology focuses on the status of governance and investment conditions in the mining sector from the perspective of stakeholders, and as reportedin primary and secondary sources.